First record of the Pacific oyster Magallana gigas (Thunberg, 1793) in the Baltic Sea proper - Ewers-Saucedo, Christine; Heuer, Nele; Moesges, Zoe; Ovenbeck, Kira; Schröter, Nicole; Brandis, Dirk (Marine Biodiversity Records, 2020)
Since its introduction in the 1960’s for aquaculture, the Pacific oyster Magallana gigas (Thunberg, 1793) has successfully spread along almost all European coasts with far-reaching consequences for marine ecosystems. Up to now, it has not been recorded from the Baltic Sea proper. This was considered a consequence of the low salinity conditions, which are not suitable for larval development. Here we report our first records of Pacific oysters in the German Baltic Sea, specifically in the Kiel Bight. We confirmed their species identification by genetic barcoding. We suggest that Pacific oysters were able to settle in the Baltic Sea proper due to unusually high salinities that prevailed since the summer of 2018. Should these conditions occur more frequently in the future, or M. gigas be able to adapt to lower salinities, oysters may become established in the Baltic Sea proper.